An Analysis of Demographic Characteristics of Students at Risk for Learning Disorders in Nam Dinh Province - Thanh Nam, Tran; Cong, Tran Van; Phuong, Nguyen Thi Hoai; Duong, Le Huy (VNU Journal of Science: Education Research, 2024)
Understanding early signs of learning disorders since children were in preschool combined with popular demographic characteristics helps detect and intervene on time and reduces harmful effects on their development. 554 parents and 38 homeroom teachers of grade 1 st and 2 nd students in Nam Dinh province participated in this study to describe family members, development, and academic achievement of students with a risk of learning disorders. The results showed that 11.7% of students had a risk of learning disorders, with 23 students having a type of learning disorders, 17 students having two types, and 25 students having all three types of learning disorders. The rate of male: female of the three groups was a range of 1.8-3.3:1. The mean age of the student’s parents with risk for a type of learning disorders was smaller than that of the two left student group’s parents. The most common early symptom before engaging in elementary school was delayed speech and difficulty in pronunciation. In addition, the analyzed data revealed that the students in Nam Dinh City had a significantly higher percentage than those in Truc Ninh and Giao Thuy.